IMPLEMENTASI SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) DALAM PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL (DISDUKCAPIL) KABUPATEN KARANGANYAR - Ambar Nur Hendras Wari; Liliek Winarni; Damayanti Suhita (Solidaritas, 2020)
Population Administration Information (SIAK) in the Electronic Resident Identity Card (e-KTP) Service in the Karanganyar Regency Population and Civil Registration Service. This type of research used in this research is descriptive qualitative. Data collection used in this study was by interview, observation and documentation. The data analysis technique used is qualitative with the approach of Miles Huberman and Sardana. The results showed that 1) Communication; transmission with socialization to sub-district and village officials clearly and consistently. 2) Resources; employee resource development is done by way of training and training. The information carried out is to conduct socialization to the public. The authority of SIAK in e-KTP services is performed by the Data Base Administrator. Facilities and infrastructure are as needed although sometimes having hardware problems. 3) Disposition; Commitments between employees in e-KTP services are carried out accurately and quickly and do not receive additional incentives that are part of the work assignments in serving the community. 4) Bureaucratic Structure; The bureaucratic structure has been carried out in accordance with the National Guidelines and technical guidelines and applicable SOPs. Fragmentation or division of responsibilities is given by the Karanganyar Regency Government through a Regional Regulation.